Phytochemical Evaluation and In vitro Antioxidant Activity of Various Solvent Extracts of Leucas aspera (Willd.) Link Leaves - Annapandian, Vellaichamy Muthupandi; Rajagopal, Shanmuga Sundaram (Free Radicals and Antioxidants)
Background: Free radicals initiate the oxidative stress and damage the healthy cells. These damages contribute ageing, cancer, cardiovascular and inflammatory diseases. Phenolic compounds, flavonoids and tannins are directly contributed to antioxidant activity. Objective: The present study was attempted to evaluate the phytochemicals present in various solvent extracts obtained from Leucas aspera (Willd) Link leaves (L. aspera) and its antioxidant activity using different in-vitro models. Materials and Methods: The free radical scavenging and antioxidant activity of petroleum ether, ethanol, isopropyl alcohol, ethyl acetate and chloroform extracts of L. aspera leaves were assessed by different in-vitro models include DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging capacity, total antioxidant activity, ABTS (2,2,-azinobis (3-ethylbenzoline-6-sulfonic acid) radical scavenging activity and nitric oxide radical inhibition assay, in order to ensure the pharmacological effects of the plant. Results: Petroleum ether extract (non-polar solvent) showed better antioxidant activity among the solvents with IC50 values 18.96 μg/mL (DPPH assay), 17.22 μg/mL (total antioxidant assay), 16.00 μg/mL (ABTS assay) and 11.87 μg/mL (nitric oxide scavenging). Whereas, ethanol extract (polar solvent) exhibited better DPPH scavenging, ABTS assay and nitric oxide scavenging activity (IC50=19.90, 11.60 and 13.47 μg/mL respectively) compared to chloroform, ethyl-acetate and isopropyl alcohol extracts. Conclusion: The results of our current study showed, L. aspera leaf is a significant source of phytochemicals that possess antioxidant and scavenging properties. Our study findings warrants for various pharmacological activities and further research on isolation and characterization of active principle responsible for the pharmacological activity.
Keywords: In vitro antioxidant; Leucas aspera; Non-polar solvent; Polar solvent; Various solvents